2017
DOI: 10.1007/s00125-017-4396-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of glycaemic and lipid risk factors in mediating the effect of BMI on coronary heart disease: a two-step, two-sample Mendelian randomisation study

Abstract: Aims/hypothesis The extent to which effects of BMI on CHD are mediated by glycaemic and lipid risk factors is unclear. In this study we examined the effects of these traits using genetic evidence. Methods We used two-sample Mendelian randomisation to determine: (1) the causal effect of BMI on CHD (60,801 case vs 123,504 control participants), type 2 diabetes (34,840 case vs 114,981 control participants), fasting glucose (n = 46,186), insulin (n = 38,238), HbA 1c (n = 46,368) and LDL-cholesterol, HDL-cholestero… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 48 publications
4
68
1
Order By: Relevance
“…In summary, the exact mechanisms remain elusive and are probably multifactorial, stemming from mechanical alterations of the airways and lung parenchyma, to systemic and airway inflammatory and metabolic dysfunction that adversely influences pulmonary function and/or response to therapy. In addition to the detrimental effects on lung function, obesity is a confirmed cause of diabetes and cardiovascular disease, leading to higher overall mortality (32)(33)(34). In our study, patients with a BMI $28 kg/m 2 were at increased odds of developing a severe case of COVID-19, which remained significant in the multivariable analysis after adjustment for reported comorbidities.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In summary, the exact mechanisms remain elusive and are probably multifactorial, stemming from mechanical alterations of the airways and lung parenchyma, to systemic and airway inflammatory and metabolic dysfunction that adversely influences pulmonary function and/or response to therapy. In addition to the detrimental effects on lung function, obesity is a confirmed cause of diabetes and cardiovascular disease, leading to higher overall mortality (32)(33)(34). In our study, patients with a BMI $28 kg/m 2 were at increased odds of developing a severe case of COVID-19, which remained significant in the multivariable analysis after adjustment for reported comorbidities.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, men had a higher prevalence of obesity than women (17.5% versus 4.5%). Obese patients also tended to have cough (P 5 0.03) and fever (P 5 0.06) as initial symptoms, compared with nonobese patients, but they were comparable in terms of other symptoms (P 5 0.09-0.81), epidemiological characteristics (P 5 0.10), personal disease history (P 5 0.15-0.82), and disease progression or treatment (P 5 0.14-0.88) ( [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] days). Three deaths occurred in the severe group, and no deaths occurred in the nonsevere group (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of mechanisms by which this is proposed to be mediated, including the stimulatory effect of insulin on fatty acid storage and cell growth and a reduction in glycosuria (75-77). Furthermore, Mendelian randomisation analyses have supported a positive relationship between insulin and weight gain (78,79). Given the nature of the clinical presentation of anorexia, the effect of insulin on hunger and satiety is particularly pertinent.…”
Section: Discussionmentioning
confidence: 99%
“…This study, as some other previous studies [23][24][25][26] , did not exclude those with pre-existing disease and smoking 9 , which might mask the BMI-mortality risk association. Moreover, inappropriate adjustment for mediating factors for the associations between BMI and major health endpoints (i.e., CVD), such as glycaemia, triglycerides and low-density lipoprotein cholesterol will attenuate the result towards the null 9,27 . One recent study in China also showed no association between greater BMI groups (i.e., BMI > 26, 28 or 30 kg/m 2 ) and all-cause mortality, in subgroups by glycaemic status or in the whole sample 15 .…”
Section: Discussionmentioning
confidence: 99%